Potential for Genetic Improvement of Resistance to Perkinsus olseni in the Manila Clam, Ruditapes philippinarum, Using DNA Parentage Assignment and Mass Spawning - Smits, Morgan; Enez, Florian; Ferraresso, Serena; Dalla Rovere, Giulia; Vetois, Emilie; Auvray, Jean-François; Genestout, Lucie; Mahla, Rachid; Arcangeli, Giuseppe; Paillard, Christine; Haffray, Pierrick; Bargelloni, Luca (Frontiers in Veterinary Science, 2020)
The Manila clam Ruditapes philippinarum, a major cultured shellfish species, is threatened by infection with the microparasite Perkinsus olseni, whose prevalence increases with high water temperatures. Under the current trend of climate change, the severe effects of this parasitic infection might rapidly increase the frequency of mortality events. Treating infectious diseases in bivalves is notoriously problematic, therefore selective breeding for resistance represents a strategy for mitigating the negative impact of pathogens. A crucial step in initiating selective breeding is the estimation of genetic parameters for traits of interest, which requires recording parentage and accurate phenotypes for numerous individuals. Here, to estimate the heritability of resistance against P. olseni, a field experiment mirroring conditions in industrial clam production was set up, a genomic tool was developed for parentage assignment, and parasite load was determined through quantitative PCR. A mixed-family cohort of potentially 1479 clam families was produced by mass spawning of 53 dams and 57 sires. The progenies were seeded in a commercial clam production area in the Venice lagoon, Italy, where high prevalence of P. olseni had previously been reported. Growth and parasite load were monitored monthly and more than 1000 individuals were collected for DNA and phenotype recording. Pooled sequencing was used for DNA samples from the broodstock and from a local clam population, providing candidate markers used to develop a 245-SNP panel. Parentage assignment for 246 F1 showed sire and dam representation were high (75 and 85%, respectively), indicating a limited risk of inbreeding. Moderate heritability (0.23 ± 0.11 – 0.35 ± 0.13) was estimated for growth traits (shell length, shell weight, total weight), while parasite load showed high heritability, at 0.51 ± 0.20. No genetic correlations were found between growth traits and parasite load. Overall, the preliminary results from this study show high potential for selecting clams resistant to parasite load. Breeding for resistance may help limit the negative effects of climate change, as the prevalence of the parasite is predicted to increase under a future high-temperature scenarios. Finally, the limited genetic correlations between traits suggests that breeding programs could incorporate dual selection without negative interactions.